U.S. global leadership role and domestic polarization: a role theory approach - Friedrichs, Gordon (Routledge, Taylor & Francis Group, 2021)
In this book Gordon Friedrichs offers a pioneering insight into the implications of domestic polarization for U.S. foreign policymaking and the exercise of America’s international leadership role. Through a mixed-method design and a rich dataset consisting of polarization data, congressional debates and letters, as well as co-sponsorship coalitions, Friedrichs applies role theory to analyze three polarization effects for U.S. leadership role-taking: a sorting effect, a partisan warfare, and an institutional corrosion effect. These effects are deployed in two comparative case studies: The Iran nuclear crisis as well as the negotiations of the Trans-Pacific Partnership Agreement. Friedrichs effectively exposes the drivers of polarization and how this extreme divergence has translated into partisan warfare as well as institutional corrosion, affecting direction and performance of the U.S. global leadership role.
Literaturangaben, Register
Keywords: United States -- Foreign relations -- 21st century; United States -- Politics and government -- 21st century; USA; Electronic books